PENGARUH PERENDAMAN TANAH DAN PEMUPUKAN TERHADAP VIRULENSI PLASMODIOPHORA BRASSICAE WOR. PADA TANAMAN CAISIN (BRASSICA CHINENSIS L.) - Supriyati, Dyah (Research Center for Biology-Indonesian Institute of Sciences, 1989)
DYAH SUPRIYATI. 1989. The influence of soil inundation and fertilizer to the pathogenecity of Plasmodiophora brassicae Wor. on caisin plant. Berita Biologi 3(9): 463 - 466: Caisin (Brassica chinensis L.) is a member of family Btassicaceae. One of the important diseases that usually attack the plant is swollen root disease (clubroot). The disease is caused by an obligate parasitic fungi i.e. Plasmodiophora brassicae Wor.The pathogen is very difficult to be destroyed, because it has resting spore that remain viable in the soil for a long time.The purpose of this study is to know the influence of soil inundation and fertilizer to the pathogenecity of P. brassicae on caisin plant. The test design is Completely Randomised Design (CRD) with two treatments , soil inundation for 5 days, 10 days, 15 days and 20 days; giving urea, TSP, KC1, mixture of urea, TSP and KC1 fertilizer, lime and control.The observation was performed when the plant has frown for 25 days in the pot. The result of observation is that the treatments with lime, mix true of urea, TSP and KC1 fertiliser, 20 days and 15 days soil inundation decrease the grade of attact of P. brassicae on caisin plant.